Enhancing Fiqh learning outcomes through artificial intelligence applications at Sekolah Indonesia Johor Bahru - Khoir, Tholkhatul; Fadzil Abdul Hanid, Mohd; Khasan, Moh; Azean Atan, Noor; Zulfa Elizabeth, Misbah; Hashim, Shahrin (Edelweiss Applied Science and Technology, 2024)
Artificial Intelligence (AI) has rapidly emerged as a transformative force in education, offering innovative solutions to enhance learning and teaching processes. This technology is revolutionising traditional educational methods by enabling more efficient, accessible, and engaging learning environments. This study aims to evaluate the impact of AI on Fiqh education at Sekolah Indonesia Johor Bahru (SIJB), reflecting the technological advancements of the Fourth Industrial Revolution. The research employs a quantitative quasi-experimental design, involving 73 students, to assess the effectiveness of AI tools in enhancing Fiqh learning outcomes. Pre-test and post-test data were analysed using the Wilcoxon Signed-Rank Test to measure the effect of AI-based interventions on student performance. The results indicate positive effects of AI-based learning methods on students in Fiqh education. Additionally, a four-point Likert scale questionnaire was used to assess students’ perceptions of the ease of use of AI tools, their understanding, and the impact of these tools on learning. The study concludes that the integration of AI tools in Fiqh education at Sekolah Indonesia Johor Bahru significantly enhances students’ knowledge and learning outcomes. The implications of these findings suggest that AI can be effectively integrated into Fiqh learning to foster a more engaging and efficient learning environment, ultimately improving student performance and understanding.